PENGARUH MORFOLOGI DAN SIFAT MATERIAL TERHADAP KESTABILAN LERENG DI KECAMATAN KALIBAWANG, KULON PROGO - Supandi, Supandi; AR, Shilvyanora; Ag, Isjudarto (Jurnal Teknologi Technoscientia, 2017)
Mass movement is one of hazard in Indonesia that have significant impact in Indonesia. This hazard caused by Indonesia represent have wet tropik, so that chemical weathering intensive and formed thick soil. Its improve the happening of crisis to this hazard, because material strength will decrease. District of Kalibawang, Kulon Progo morphologicaly have a lot precipitous slope and mount intensive weathering. This condition constituing study concerning slope stability. Method which used in this analysis is slice method with approach of calculation of made moderate Bishop. This method weared many in analysis stability of slope because besides modestly, this method enough is accurate. Than analysis slope stability of some obtained chosen slope have value between 3.378 (stable) until 1.052 is ( labile / critical)